The counter-claim in litigation about international contracts of employment. (Commentary to EUCJ judgment 21 June 2018, case C-1/17, Petronas Lubricants Italy) - Espiniella Menéndez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
in its Judgment of 21 June 2018, in case Petronas Lubricants Italy, the EUCJ affirms the viability of a counterclaim by the employer against the worker with respect to credits assigned by another employer. The Judgment has positive aspects, due to it consolidates the jurisdiction of the initial court for a counterclaim for reasons of procedural economy, even when the counterclaimant is a stronger legal and economic party, such as an employer. Also it is positive to require that the counterclaim has a common origin to the initial claim, because this jurisdiction rule keeps the purpose of seeking coherent decisions. Among the negative aspects, the Court, when applies the general doctrine to the specific case, legitimizes an abusive situation. The counterclaimant is using the network of group companies in order to design the counterclaim by an assignment of credits that affects the procedural position of the counterclaim defendant. That occurs when this counterclaim defendant does not participate in said assignment (it is an external act) and cannot even calculate its effects, since it is subsequent to the filing of the initial claim.
Keywords: contract of employment; international jurisdiction; counter-claim; Brussels I.a Regulation